(untitled) (Research, Society and Development, 2021)
To analyze the positivity and risk factors associated with infection of schistosomesis mansoni and enteroparasitosis in an endemic area, Sergipe, Brazil. This is a cross-sectional study. The study involved 160 residents of the village of Siebra, located in the rural area of the municipality of Maruim, Sergipe. The positivities for Schistosoma mansoni and/or enteroparasites were identified using the Kato-Katz method and ritchie’s method, respectively, and correlated with the socio-environmental conditions of the region. Regarding the positivity for schistosomes was 49.37%; infection prevailed in males (52.70%); in the elderly (77.77%). The greatest risks of becoming infected with Schistosoma mansoni were in male individuals, of age (up to 9 to >40 years), who live in rural areas, receive government help, who have constant contact with natural waters and who receive information about parasitosis. As for the samples analyzed for enteroparasitosis, the protozoa Endolimax nana and Giardia lamblia (97.52% and 78.75%) were the most prevalent; Endolimax nana was more prevalent in all ranges; infection prevailed in females (42.52%) for Trichuris trichiura, 9.19% for Enterobius vermiculars, 67.81% for Entamoeba histolytica, 85.05% for Giardia lamblia, 88.50% for Entamoeba coli and 86.20% for Blastocytis hominis). The study revealed that Maruim is endemic for schistostosis and enteroparasitasis and that socio-environmental and sanitary conditions contribute to high positivity rates. The results show the need to strengthen health programs with the objective of reducing transmission and sensitizing the population in relation to these diseases.